STRATEGI PEMASARAN DALAM MENARIK MINAT BELI KONSUMEN PADA PRODUK KERIPIK AMANDA PAPAR KABUPATEN KEDIRI - Mochamad Zakky Akhiyarulloh Rosada; Miftahul Munir; Rafikhein Novia Ayuanti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research uses a type of field research (field research) with a qualitative approach. The methods used in this research are observation and interviews. Then the collected data was analyzed descriptively using qualitative analysis techniques to produce research findings about the marketing strategies implemented by Tempe MSMEs in Kediri to attract consumer buying interest. This research was conducted at the Amanda Tempe Chips MSME company located in Papar, Kediri Regency Based on the data obtained in the field, the author can conclude the marketing strategy for Amanda Tempe Chips in attracting consumer buying interest, which includes the use of organic ingredients and a focus on taste quality, expansion into export markets with strict monitoring of quality, and product innovation through diversification of new flavor variants. This strategy is expected to strengthen the market position of these MSMEs amidst intense competition and dynamic changes in the organic food industry.